ERCC1 and BRCA1 mRNA expression levels in metastatic malignant effusions is associated with chemosensitivity to cisplatin and/or docetaxel - Wang, Lifeng (BioMed Central, 2008)
BACKGROUND: One of the major challenges in currently chemotherapeutic theme is lacking effective biomarkers for drug response and sensitivity. Our current study focus on two promising biomarkers, ERCC1 (excision repair cross-complementing group 1) and BRCA1 (breast cancer susceptibility gene 1). To investigate their potential role in serving as biomarkers for drug sensitivity in cancer patients with metastases, we statistically measure the mRNA expression level of ERCC1 and BRCA1 in tumor cells isolated from malignant effusions and correlate them with cisplatin and/or docetaxel chemosensitivity. METHODS: Real-time quantitative PCR is used to analysis related genes expression in forty-six malignant effusions prospectively collected from non-small cell lung cancer (NSCLC), gastric and gynecology cancer patients. Viable tumor cells obtained from malignant effusions are tested for their sensitivity to cisplatin and docetaxel using ATP-TCA assay. RESULTS: ERCC1 expression level is negatively correlated with the sensitivity to cisplatin in NSCLC patients (P = 0.001). In NSCLC and gastric group, BRCA1 expression level is negatively correlated with the sensitivity to cisplatin (NSCLC: P = 0.014; gastric: P = 0.002) while positively correlated with sensitivity to docetaxel (NSCLC: P = 0.008; gastric: P = 0.032). A significant interaction is found between ERCC1 and BRCA1 mRNA expressions on sensitivity to cisplatin (P = 0.010, n = 45). CONCLUSION: Our results demonstrate that ERCC1 and BRCA1 mRNA expression levels are correlated with in vitro chemosensitivity to cisplatin and/or docetaxel in malignant effusions of NSCLC and gastric cancer patients. And combination of ERCC1 and BRCA1 may have a better role on predicting the sensitivity to cisplatin than the single one is considered.